DEIXIS ANALYSIS IN FANTASTIC BEAST 3: PRAGMATIC APPROACH - Rihlatul Karimah; Zeny Luthvia (Universitas Duta Bangsa Surakarta, 2023)
This study reveals about the study of deixis through a pragmatic view in the film Fantastic Beasts 3, about the use of deixis by the actors through the speech used. In this case, the writer uses a descriptive method with the following steps: 1) preparation, 2) data collection, and 3) data analysis. The results showed that the most frequent type of deixis used in the film was third person (35.90%), followed by first person (23.08%) and second person (20.51%). Time deixis (5.13%) of the total instances, while place deixis and discursive deixis comprised (12.82%) and (2.56%), respectively. Besides this the result of analysis of this study indicate that the deixis research in this film is related to the moral message that will be conveyed in the story, namely the importance of loyalty, courage, honesty and the struggle against evil enemies. An analysis of the use of deixis in this film gives us a deeper understanding of the characters, their motivations and relationships with one another to the hidden moral messages in their dialogues.